Managing soil and its nutrients for bumper harvest - Kotur, S C; Iyengar, BRV (Indian Horticulture, 2019)
The IIHR, Bengaluru, has been providing excellent leadership in understanding the issues of soil fertility and plant nutrition related to horticultural crops. The state-of-the-art facilities developed include: (i) soil chemistry, (ii) soil salinity, (iii) micronutrients, (iv) leaf analysis, (v) isotope and (vi) water management and (vi) soil microbiology and biofertilizers laboratories. In addition to recognizing the unique nature of fruit and vegetable crops, attendant problems are being addressed in a continuous and concerted manner, remedies developed and extended to the growers to achieve high yield of good quality ensuring economic and eco-friendly input use and sustenance of optimum soil health.